Effect of oxic and anoxic conditions on intracellular storage of polyhydroxyalkanoate and polyphosphate in Magnetospirillum magneticum strain AMB-1 - Su, Qingxian; Andersen, Henrik Rasmus; Bazylinski, Dennis A.; Jensen, Marlene Mark (Frontiers in Microbiology, 2023)
Magnetotactic bacteria (MTB) are microorganisms widely inhabiting the oxic-anoxic interface of aquatic environments. Beside biomineralizing magnetic nanocrystals, MTBs are able to sequester various chemical elements (e.g., carbon and phosphorus) for the biogenesis of intracellular granules, like polyhydroxyalkanoate (PHA) and polyphosphate (polyP), making them potentially important in biogeochemical cycling. Yet, the environmental controls of intracellular storage of carbon and phosphorus in MTB remain poorly understood. Here, we investigated the influence of oxic, anoxic and transient oxic-anoxic conditions on intracellular storage of PHA and polyP in Magnetospirillum magneticum strain AMB-1. In the incubations with oxygen, transmission electron microscopy revealed intercellular granules highly rich in carbon and phosphorus, which were further interpreted as PHA and polyP based on chemical and Energy-Dispersive X-ray spectroscopy analysis. Oxygen had a strong effect on PHA and polyP storage in AMB-1 cells, as PHA and polyP granules accounted for up to 47 ± 23% and 5.1 ± 1.7% of the cytoplasmic space, respectively, during continuous oxic conditions, while granules disappeared in anoxic incubations. Poly 3‑hydroxybutyrate (PHB) and poly 3‑hydroxyvalerate (PHV) accounted for 0.59 ± 0.66% and 0.0033 ± 0.0088% of dry cell weight, respectively, in anoxic incubations, while the values increased by a factor of 7 and 37 after oxygen was introduced. The results highlight a tight link between oxygen, carbon and phosphorus metabolisms in MTB, where favorable oxic growth conditions can lead to metabolic induction of polyP and PHA granule biogenesis.